Menuju Puncak Sukses: Transformasi Mimpi melalui Pendidikan Vokasi - Romadhon, Romadhon (Universitas Bunda Mulia, 2024)
The Community Service Activity (PKM) held at the Algaf Building, Politeknik Piksi Input Serang, was an initiative designed to motivate and enlighten high school graduates from SMA/SMK/MA/equivalent about the importance of higher education, especially in vocational fields. Attended by 225 participants, including students and teachers from various regions of Serang, as well as lecturers and educational staff from Politeknik Piksi Input Serang, the event offered a series of presentations, lectures, group discussions, and in-depth Q&A sessions. The goal was to broaden participants' perspectives on the opportunities and career prospects achievable through vocational education. Additionally, a campus tour provided a tangible overview of the learning environment and available facilities, stimulating participants' interest in pursuing further education. While the event was successful in delivering information and motivation, it fell short in allocating sufficient time for direct interaction, necessitating future adjustments. Suggestions for improvement include extending the time for discussion sessions and utilizing information technology to maximize participant engagement and satisfaction.